2001
DOI: 10.1063/1.1426257
|View full text |Cite
|
Sign up to set email alerts
|

Boron carbide/n-silicon carbide heterojunction diodes

Abstract: Adenwalla, Shireen; Welsch, P.; Harken, A.; Brand, Jennifer I.; Sezer, A.; and Robertson, Brian W., "Boron carbide/n-silicon carbide heterojunction diodes" (2001). Faculty Publications from Nebraska Center for Materials and Nanoscience. 85.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 6 publications
1
67
1
Order By: Relevance
“…The neutron capture reaction in the BC/Si heterojunction detector for thermal neutrons is described in equation (1) and illustrated in figure 1. Neutron capture occurs only in the ptype BC side, with the neutron capture site serving as the origin for highly energetic 7 Li and 4 He ions, emitted back-to-back.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutron capture reaction in the BC/Si heterojunction detector for thermal neutrons is described in equation (1) and illustrated in figure 1. Neutron capture occurs only in the ptype BC side, with the neutron capture site serving as the origin for highly energetic 7 Li and 4 He ions, emitted back-to-back.…”
Section: Introductionmentioning
confidence: 99%
“…Few elements possess a significant capture cross section for thermal neutrons, and among these elements, those suitable for forming a semiconducting solid are rare indeed. Boron is uniquely suitable, having a large capture cross section for thermal neutrons, generating high energy ions that are easily detectable on neutron capture and forming a boron rich semiconducting solid, boron carbide (BC) [1,2], grown by plasma enhanced chemical vapor deposition (PECVD). The growth and properties of a semiconducting form of BC have been intensively studied for the last 20 years, resulting in heterojunction and homojunction diodes [1,[3][4][5][6][7], Esaki tunnel diodes [8], and, most relevant for this manuscript, solid state neutron detectors [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…When the source molecules closo 1,2-dicarbadodecaborane ͑orthocarborane͒ and closo 1,7-dicarbadodecaborane ͑metacarborane͒, shown inset to Figs. 1 and 2, are decomposed by synchrotron light ͑or electron beam induced decomposition͒, forming two of the many C 2 B 10 polytypes of boron-carbide, 14 respective shifts toward lower and higher binding energy are incurred.…”
mentioning
confidence: 99%
“…These materials may be useful in electronic devices operating in a wide variety of extreme or harsh environments (mechanically abrasive, radiative, corrosive, and/or high temperature). Implementation of these materials will require a thorough understanding of their electrical properties, which are profoundly influenced by their composition, 6,7 microstructure, 5 and deposition methods. 8 Considerable research has focused on the electrical transport mechanism, 6 dielectric properties, 7 doping behavior, 9,10 and device performance 3,5 of boron compounds with C, N, and O, such as B 4 C/B 5 C, B x N ͑x Ͼ 1͒ and boron suboxide ͑B x O,x Ͼ 1͒.…”
mentioning
confidence: 99%
“…Implementation of these materials will require a thorough understanding of their electrical properties, which are profoundly influenced by their composition, 6,7 microstructure, 5 and deposition methods. 8 Considerable research has focused on the electrical transport mechanism, 6 dielectric properties, 7 doping behavior, 9,10 and device performance 3,5 of boron compounds with C, N, and O, such as B 4 C/B 5 C, B x N ͑x Ͼ 1͒ and boron suboxide ͑B x O,x Ͼ 1͒. Recently, the ternary boride compound AlMgB 14 has attracted attention due to its interesting mechanical properties; 11,12 however, no studies have been reported on the electrical properties of AlMgB 14 thin films.…”
mentioning
confidence: 99%